Engineering synthetic signaling receptors to enable erythropoietin-free erythropoiesis - Aadit P. Shah; Kiran R. Majeti; Freja K. Ekman; Sridhar Selvaraj; Devesh Sharma; Roshani Sinha; Eric Soupene; Prathamesh Chati; Sofia E. Luna; Carsten T. Charlesworth; Travis McCreary; Benjamin J. Lesch; et al. (Nature Communications)
Abstract Blood transfusion plays a vital role in modern medicine, but frequent shortages occur. Ex vivo manufacturing of red blood cells (RBCs) from universal donor cells offers a potential solution, yet the high cost of recombinant cytokines remains a barrier. Erythropoietin (EPO) signaling is crucial for RBC development, and EPO is among the most expensive media components. To address this challenge, we develop highly optimized small molecule-inducible synthetic EPO receptors (synEPORs) using design-build-test cycles and genome editing. By integrating synEPOR at the endogenous EPOR locus in O-negative induced pluripotent stem cells, we achieve equivalent erythroid differentiation, transcriptomic changes, and hemoglobin production using small molecules compared to EPO-supplemented cultures. This approach dramatically reduces culture media costs. Our strategy not only addresses RBC production challenges but also demonstrates how protein and genome engineering can introduce precisely regulated cellular behaviors, potentially improving scalable manufacturing of a wide range of clinically relevant cell types.